Former corporate managers, fiduciary obligations, and the public policy in favor of competition - Welling, Bruce (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1990)
In common law sytstems corporate managers owe fiduciary obligations to their corporations. This has complicated the legal analysis of competitive business activities by former corporate managers, particularly since the 1974 Supreme Court of Canada decision in Canaero. Other former corporate employees have long been allowed to compete with their ex-employers, so long as they do not use their ex-employers' property or breach terms of any contracts restraining their business activities. Attempts to contract to restrain future competitive business activities have long been restricted by the public policy in favor of competition. Former corporate managers can also be sued in Equity : the remedy is for an accounting of profits or for equitable damages. The judicial analysis of these equitable actions has been mystified by the "corporate opportunity doctrine" and the mistaken notion that a fiduciary obligation can survive resignation from the fiduciary position that created the obligation. A review of the basics exposes the errors and shows that equitable accounting and equitable damages remedies are also subject to the public policy in favor of competition, but that the calculation is more complicated than in contracts.